(3eGgjI GdGdJRGe HGdSQjI h GdeSFhdjI GdeOfjI GdfGTFI Yf GdENdGd Hg (B: s (3OQGSI ebGQfI (B/ s - (3eMeO EHQGgje EHQGgje MSGfjfs; (3fRjg eMeO GdUGOb GdegOjs; (3LGeYI GdbGgQI s (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B-(3LGeYI GdbGgQI,s, 2013)
(3YGdLJ GdOQGSI ehVhY eGgjI GdGdJRGe HGdSQjI h GdeSFhdjI GdeOfjI GdfGTFI Yf GdENdGd Hg (B- (3OQGSI ebGQfI(B) (3ef NdGd HGHjf JMOKfG Yf eGgjI GdGdJRGe HGdSQjI(B: (3aGVWdYfG HJYQja GdSQ h eVehf GdGdJRGe HGdSQjI h eUGOQ gPG GdGdJRGe(B: (3h GdGSJKfGAGJ ef NdGd MGdGJ GdEaTGA GdhLhHj h GdEaTGA GdLhGRj(B: (3Ke GdMOjK Yf GdeSFhdjI GdeOfjI h JWhQgG aj eLGd GdGdJRGe HGdSQjI ef NdGd HYV GdJWHjbGJ(B. (3h bO JhUdfG Edi YOI JhUjGJ CgegG hLhH GdJhSY aj JWHjb GdeSFhdjI GdehVhYjI aj eLGd GdGdJRGe HGdSQjI(B: (3h Pdc JCcjOG dacQI GdVeGf h JMed GdJHYI(B: (3cPdc VQhQI Cf VQhQI Cf jfU GdeTQY HbhGfjf NGUI Ydi MeGjI GdMb aj GdNUhUjI h GdGdJRGe HGdSQjI(B.s
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI, cdjI GdMbhb, bSe GdbGfhf GdeOfi (B2013.s
(3HHdjhLQGajG(B: (3UaMGJ (B367-398.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3CMcGe GdGdJRGes; (3GdSQjIs; (3GdeSFhdjI GdeOfjIs; (3GdGdJRGe HGdSQjIs; (3GdeSFhdjI GdeOfjI ddGNdGd HGdGdJRGe HGdSQjIs; (3GdGSJKfGAGJ GdhGQOI Ydi GdGdJRGe HGdSQjIs; (3EaTGA GdCSQGQs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdeOfjs